Biocrust as a surface protection of erodible nebkhas - Tan, Ning‐Jing; Luo, Xiao‐Mei; Wang, Zhen‐Ting (Earth surface processes and landforms, 2024)
Since the timescale of a nebkha from the initial formation to the eventual destruction might be 1 to 200 years, little is known about the whole evolutionary path. In the phase of erosion and deflation, nebkhas are usually one source of aeolian sand and dust. Biocrust, a common living cover in arid and semiarid regions, could influence dune dynamic. In this study, the shear strength and hardness of the windward slope surface of erodible nebkhas are measured in the upwind margin of the Minqin oasis, China. It is found that both the shear strength and hardness of topsoil are commonly larger than these under the biocrust layer. From the force‐balance equation about the vane shear test, a novel expression for the shear strength of biocrust is derived. The field experiment in the windy season of 2023 shows that the biocrust layer of topsoil can effectively increase the resistance of nebkha surface against wind erosion. The relative larger strength and the self‐repair function of biocrust supported by the local non‐rain water are two main reasons the erodible nebkhas can exist for decades. A novel expression for the shear strength of biocrust is derived from the force‐balance equation about the vane shear test. The biocrust layer can effectively increase the resistance of nebkha surface against wind erosion. Continuously supported by biocrusts, erodible nebkhas might exist for decades.